Testicular Toxicity. An International Consortium for Innovation and Quality in Pharmaceutical Development (IQ) DruSafe Industry-Wide Survey - Reginald A. Valdez; Angela Stermer; Manoj Bhaskaran; Sarah Campion; Karyn Colman; Anthony M. DeLise; Edward Dere; Brian Enright; Ellen McGlinchey; Stephanie Rayhon; Dinesh Stanislaus; Takayuki Tsuchiya; et al. (Regulatory Toxicology and Pharmacology, 2026)

Optimising ecological and engineering outcomes of hybrid mangrove living shorelines using life-cycle informed restoration - Roma O. Bodycomb; Stephen E. Swearer; Andrew W.M. Pomeroy; Brendan S. Lanham; Melanie J. Bishop; Victoria J. Cole; Nicholas Colman; Marco Ghisalberti; Jack Grant; Brian Hughes; Charlotte A. Jenkins; Ryan J. Lowe; et al. (Journal of Environmental Management, 2026)

Exposure to low-dose ionizing radiation and dementia mortality in Canadian nuclear power plant workers - Brianna Frangione; Laura A. Rodriguez Villamizar; Ian Colman; Franco Momoli; Estelle Davesne; Lydia Zablotska; Cheryl E. Peters; Paul Demers; Minh Do; Tim Prendergast; Philippe Prince; Paul J. Villeneuve (Environmental Research, 2026)

Environmental degradation in the middle basin of Conchitas river, Buenos Aires: Two decades of urban and industrial pressure - Micaela A. Mujica; María Belén Sathicq; María Mercedes Nicolosi Gelis; Lucía Galli; Hugo Daniel Di Giorgi; Jimena Camila Suárez; Esteban Jorge Colman Lerner; Sebastián Besteiro; Fernanda Julia Gaspari; Joaquín Cochero (Environmental Science and Pollution Research, 2026)

Chitosan Nanofibrous Dressing Increased Angiogenesis and Anti-inflammatory Response in an Acute Wound Model in Rats: A Comparative Study - Yury Salkovskiy; Mahboubeh Ghanbari; Carlos P. Jara; Sara Cartwright; Pinaki Mondal; Colman Freel; Sayed Ahmadreza Razian; Jason MacTaggart; Mark A. Carlson (Annals of Biomedical Engineering, 2025)
Purpose Chitosan-based materials are promising for wound healing because of their antibacterial efficacy, biocompatibility, and biodegradability, though their healing mechanisms remain unclear. This study explores the cellular and molecular mechanisms of wound healing with chitosan nanofibrous dressings. Methods Thirty-nine Sprague Dawley rats were divided into three groups based on the type of dressings administered: (1) chitosan nanofibrous dressing + transparent film, (2) commercial scaffold + transparent film, and (3) transparent film alone (control). Full-thickness wounds (2 cm × 2 cm) were created on the dorsum, splinted, and covered with dressings. Evaluations at 7, 14, and 21 days included histological analysis, and measurements of TNF-α and iNOS levels in the wounds. Results On day 21, epithelialization was significantly higher in the chitosan group than in the scaffold group (87.5% vs. 42.0%, p = 0.03). TNF-α levels were lower in both treatment groups compared to the controls. In the chitosan group, the CD68+/CD163+ ratio was lower than in the scaffold group (0.28 vs. 0.62, p = 0.037), and blood vessel formation was greater than in the controls. Conclusion These results suggest that chitosan nanofibrous dressings enhance acute wound healing in rats by promoting re-epithelialization, neovasculogenesis, and maintaining low TNF-α levels in the later phases of healing.

Widespread presence of potato virus Y in the main potato-producing region of Paraguay - Diana C. Zorrilla; Marcelo Alborno-Jover; Yerutí Mongelos-Franco; Blanca Coronel; Heron Kraide; Lino Ramirez-Ayala; Adans Colman; Jorge A. M. Rezende; Elliot W. Kitajima; Alfredo Gryciuk Almeida; Arnaldo Esquivel-Fariña (Journal of Plant Pathology, 2025)

Comparative lifespan and healthspan of nonhuman primate species common to biomedical research - Hillary F. Huber; Hannah C. Ainsworth; Ellen E. Quillen; Adam Salmon; Corinna Ross; Adinda D. Azhar; Karen Bales; Michele A. Basso; Kristine Coleman; Ricki Colman; Huda S. Darusman; William Hopkins; et al. (GeroScience, 2024)

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

The dynamic influence of subsurface geological processes on the assembly and diversification of thermophilic microbial communities in continental hydrothermal systems - Kenneth W.W. Sims; Cole M. Messa; Sean R. Scott; Andrew D. Parsekian; Andrew Miller; Abraham L. Role; Timothy P. Moloney; Everett L. Shock; Jacob B. Lowenstern; R. Blaine McCleskey; Matthew A. Charette; Bradley J. Carr; et al. (Geochimica et Cosmochimica Acta, 2023)

Diverse skill of seasonal dynamical models in forecasting South Asian monsoon precipitation and the influence of ENSO and IOD - J. Stacey; K. Salmon; T. Janes; A. Colman; F. Colledge; P. E. Bett; G. Srinivasan; D. S. Pai (Climate Dynamics, 2023)
The South Asia Seasonal Climate Outlook Forum (SASCOF) issues seasonal tercile precipitation forecasts to provide advance warning of anomalously dry or wet monsoon seasons in South Asia. To increase objectivity of the SASCOF seasonal outlook, the World Meteorological Organisation recommends using a multi-model ensemble combining the most skilful dynamical seasonal models for the region. We assess the skill of 12 dynamical models at forecasting seasonal precipitation totals for 1993–2016 for the southwest (June–July–August–September) and northeast (October–November–December) monsoon seasons at regional and national levels for Afghanistan, Bangladesh, Nepal, and Pakistan, using identical forecast periods, hindcast initialisation months and domain used at the SASCOF. All models demonstrate positive skill when regionally-averaged, especially for the southwest monsoon season, noting considerable spatial differences. Models exhibit highest skill where correlation between observed precipitation and El Niño Southern Oscillation (ENSO) is highest, e.g., central/north India and Nepal during the southwest monsoon, and Afghanistan and north Pakistan during the northeast monsoon. Model skill is especially low in northwest India and northeast of South Asia during the southwest monsoon, e.g., Bangladesh (despite high precipitation totals) coinciding with a weak ENSO teleconnection. The Indian Ocean Dipole teleconnection is less pronounced in the southwest monsoon season, whereas the spatial pattern for the northeast monsoon closely resembles that of ENSO. Due to high variability in model skill, we recommend basing the SASCOF forecast on a multi-model ensemble of all models but discounting poorly performing models at the national level.

Distribution and abundance of tetraether lipid cyclization genes in terrestrial hot springs reflect pH - Laura N. Blum; Daniel R. Colman; Emiley A. Eloe‐Fadrosh; Matthew Kellom; Eric S. Boyd; Olga Zhaxybayeva; William D. Leavitt (Environmental Microbiology, 2023)
Many Archaea produce membrane‐spanning lipids that enable life in extreme environments. These isoprenoid glycerol dibiphytanyl glycerol tetraethers (GDGTs) may contain up to eight cyclopentyl and one cyclohexyl ring, where higher degrees of cyclization are associated with more acidic, hotter or energy‐limited conditions. Recently, the genes encoding GDGT ring synthases, grsAB , were identified in two Sulfolobaceae; however, the distribution and abundance of grs homologs across environments inhabited by these and related organisms remain a mystery. To address this, we examined the distribution of grs homologs in relation to environmental temperature and pH, from thermal springs across Earth, where sequences derive from metagenomes, metatranscriptomes, single‐cell and cultivar genomes. The abundance of grs homologs shows a strong negative correlation to pH, but a weak positive correlation to temperature. Archaeal genomes and metagenome‐assembled genomes (MAGs) that carry two or more grs copies are more abundant in low pH springs. We also find grs in 12 archaeal classes, with the most representatives in Thermoproteia, followed by MAGs of the uncultured Korarchaeia, Bathyarchaeia and Hadarchaeia, while several Nitrososphaeria encodes >3 copies. Our findings highlight the key role of grs ‐catalysed lipid cyclization in archaeal diversification across hot and acidic environments.

CRISPR/Cas9-mediated phospholipase C 2 knock-out tomato plants are more resistant to Botrytis cinerea - Enzo A. Perk; Andrés Arruebarrena Di Palma; Silvana Colman; Oriana Mariani; Ignacio Cerrudo; Juan Martín D’Ambrosio; Luciana Robuschi; Marina A. Pombo; Hernán G. Rosli; Fernando Villareal; Ana M. Laxalt (Planta, 2023)

Daily changes in ambient air pollution concentrations and temperature and suicide mortality in Canada: Findings from a national time-stratified case-crossover study - Paul J. Villeneuve; David Huynh; Éric Lavigne; Ian Colman; Hymie Anisman; Cheryl Peters; Laura A. Rodríguez-Villamizar (Environmental Research, 2023)

Ecological risk assessment of pesticides in sediments of Pampean streams, Argentina - M.R. Fernández San Juan; S.M.L. Lavarías; V. Aparicio; K.E. Larsen; J.E. Colman Lerner; A. Cortelezzi (Chemosphere, 2023)

Ascertainment rate of SARS-CoV-2 infections from healthcare and community testing in the UK - Ewan Colman; Gavrila A. Puspitarani; Jessica Enright; Rowland R. Kao (Journal of Theoretical Biology, 2023)

Effect of starvation and pesticide exposure on neutral lipid composition of the digestive gland of males of the apple snails Pomacea canaliculata - S.M.L. Lavarías; G.B. Peterson; L.C. Lagrutta; C. Tropea; J.E. Colman Lerner; A. Rodrigues Capítulo; A. Ves-Losada (Aquatic Toxicology, 2023)

Social integration of translocated wildlife: a case study of rehabilitated and released elephant calves in northern Kenya - Shifra Z. Goldenberg; Stephen M. Chege; Nelson Mwangi; Ian Craig; David Daballen; Iain Douglas-Hamilton; Nadine Lamberski; Moses Lenaipa; Reuben Lendira; Colman Lesowapir; Lekilia P. Lokooria; Mathew Mutinda; et al. (Mammalian Biology, 2022)
Conservation translocations have the potential to strengthen populations of threatened and endangered species, but facilitating integration of translocated individuals with resident populations remains a substantial challenge. Developing functional social relationships like cooperative partnerships or establishing clear dominance hierarchies may be critical to integration of released individuals. Developing such relationships has not received much attention in translocation research, especially for long-lived, socially complex animals for which establishment and navigation of social environments is often a lengthy process that requires sustained monitoring to understand. Here, we present a case study of the social associations of African savannah elephant ( Loxodonta africana ) calves that have been rehabilitated and released into a fenced wildlife sanctuary in northern Kenya with a resident population of elephants. We use focal follows of interactions pre-release and GPS tracking post-release to quantify social associations of calves with each other and with resident elephants at the release site. We demonstrate how this approach supports translocation monitoring by capturing temporal trends in social patterns within and between release cohorts and among released elephants and wild elephants already resident at the site during a transitional soft release period. Our results show that initial post-release social behavior of rehabilitated calves is related to histories of interaction with familiar individuals and cohort membership and that released calves increased their associations with residents over time. This information provides new behavioral insights for guiding elephant release projects, like the strength of relationships within and among release cohorts, the time to integration with the resident population, and the occurrence and increased incidence of societal fission–fusion. Further, this study provides an example of the utility of animal behavior research to achieve and assess progress towards conservation objectives, and to develop monitoring tools for conservation managers.

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Trichoderma species show biocontrol potential against Ceratocystis wilt in mango plants - R. A. S. Brito; G. P. Cavalcante; V. M. Stock; A. A. Colman; D. P. dos Santos; R. A. Sermarini; L. A. Maffia (European Journal of Plant Pathology, 2020)

Characterization of functionalized bentonite as nanocarrier of salicylic acid with protective action against Pseudomonas syringae in tomato plants - Andrea Y. Mansilla; María F. Salcedo; Silvana L. Colman; Merari T. Chevalier; Matias R. Lanfranconi; Vera A. Alvarez; Claudia A. Casalongué (European Journal of Plant Pathology, 2020)

Monitoring human genotoxicity risk associated to urban and industrial Buenos Aires air pollution exposure - María de los A. Gutiérrez; Mónica A. Palmieri; Daniela S. Giuliani; Jorge E. Colman Lerner; Guillermo Maglione; Darío Andrinolo; Deborah R. Tasat (Environmental Science and Pollution Research, 2020)

Informing CITES Parties: Strengthening science‐based decision‐making when listing marine species - Kim Friedman; Matias Braccini; Matthew Bjerregaard‐Walsh; Ramón Bonfil; Corey J. A. Bradshaw; Stephen Brouwer; Ian Campbell; Rui Coelho; Enric Cortés; Wetjens Dimmlich; Michael G. Frisk; Irene Kingma; et al. (Fish and Fisheries, 2020)
International trade in vulnerable marine species is regulated once they are listed in CITES Appendices (the Convention on International Trade in Endangered Species of Wild Fauna and Flora). Parties to the Convention submit proposal(s) 150 days prior to the CITES Conference for voting on the inclusion of new species in Appendices I and II, making a case for why CITES listing criteria are met in each case. Before the vote, Parties receive advice from (a) the Food and Agriculture Organization of the United Nations, (b) the International Union for Conservation of Nature—TRAFFIC and (c) the CITES Secretariat, among others. This paper offers an expert review of listing processes, which are the subject of much debate in fishery and environment‐protection communities, looking at two specific cases: silky shark ( Carcharhinus falciformis, Carcharhinidae) and bigeye thresher shark ( Alopias superciliosus, Alopiidae). The reviewers determine that the evidence made available to voting Parties is substantial, but suffers from non‐standard presentation across assessments. The best available data are not always presented or described transparently in relation to CITES criteria. An extension of the assessment period, as well as the opportunity to refute evidence, has been suggested as ways to support more informed and effective decision‐making by CITES Parties, whose composition of delegations varies greatly in their experience of marine species management and trade. Experts welcomed a greater coherence of advice between fishery and non‐fishery sources in the long term, and proposed a range of suggested improvements for the delivery of information and advice to CITES Parties.

Isotope ecology detects fine-scale variation in Svalbard reindeer diet: implications for monitoring herbivory in the changing Arctic - Lily Z. Zhao; Albert S. Colman; R. Justin Irvine; Stein Rune Karlsen; Gerard Olack; Erik A. Hobbie (Polar Biology, 2019)

On the influence of simulated SST warming on rainfall projections in the Indo-Pacific domain: an AGCM study - Huqiang Zhang; Y. Zhao; A. Moise; H. Ye; R. Colman; G. Roff; M. Zhao (Climate Dynamics, 2018)

Cranial Shape and the Modularity of Hybridization in Dingoes and Dogs; Hybridization Does Not Spell the End for Native Morphology - William C. H. Parr; Laura A. B. Wilson; Stephen Wroe; Nicholas J. Colman; Mathew S. Crowther; Mike Letnic (Evolutionary Biology, 2016)

Diurnal and tidal patterns of carbon uptake and calcification in geniculate inter‐tidal coralline algae - Sophie J. McCoy; Catherine A. Pfister; Gerard Olack; Albert S. Colman (Marine Ecology, 2016)
Research on coralline algal responses to ocean acidification and other environmental stressors has increased in recent years as coralline algae is thought to stand a higher chance of being affected by acidification stress than other macroalgae. To provide context and enhance the existing eco‐physiological framework for climate change studies, it is important to understand the effects of non‐extreme stressors experienced regularly by inter‐tidal coralline algae. In this study, we tested the potentially interacting effects of diurnal and tidal treatments on calcification in the geniculate coralline algae Corallina frondescens and Corallina vancouveriensis using 13 C‐labeled bicarbonate. Both species deposited more calcium carbonate during the day than at night, and also when submerged (high tide) compared with when emerged (low tide) in their apical and mature segments (intergenicula). These results indicate that inter‐tidal coralline algae do in fact pay a cost for living inter‐tidally at the edge of an adaptive zone.

Uncertainty in CMIP5 model-projected changes in the onset/retreat of the Australian summer monsoon - Huqiang Zhang; Guangtao Dong; A. Moise; R. Colman; L. Hanson; H. Ye (Climate Dynamics, 2016)

Abrupt deglaciation on the northeastern Tibetan Plateau: evidence from Lake Qinghai - Xiuju Liu; Steven M. Colman; Erik T. Brown; Andrew C. G. Henderson; Josef P. Werne; Jonathan A. Holmes (Journal of Paleolimnology, 2014)

The South Pacific Convergence Zone in CMIP5 simulations of historical and future climate - Josephine R. Brown; Aurel F. Moise; Robert A. Colman (Climate Dynamics, 2013)

Neuronal sirtuin1 mediates retinal vascular regeneration in oxygen-induced ischemic retinopathy - Jing Chen; Shaday Michan; Aimee M. Juan; Christian G. Hurst; Colman J. Hatton; Dorothy T. Pei; Jean-Sebastien Joyal; Lucy P. Evans; Zhenghao Cui; Andreas Stahl; Przemyslaw Sapieha; David A. Sinclair; et al. (Angiogenesis, 2013)

On atmospheric radiative feedbacks associated with climate variability and change - R. A. Colman; L. I. Hanson (Climate Dynamics, 2013)

Symbiodinium diversity in the soft coral Heteroxenia sp. and its nudibranch predator Phyllodesmium lizardensis - S. K. FitzPatrick; K. L. Liberatore; J. R. Garcia; I. Burghardt; D. R. Colman; S. A. Moquin; C. D. Takacs-Vesbach; U. L. Shepherd (Coral Reefs, 2012)

Multiple Effects of Changes in Arctic Snow Cover - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Raymond S. Bradley; Sylvie Blangy; Olga N. Bulygina; Torben R. Christensen; Jonathan E. Colman; Richard L. H. Essery; et al. (Ambio, 2011)

On tropospheric adjustment to forcing and climate feedbacks - R. A. Colman; B. J. McAvaney (Climate Dynamics, 2011)

Atmospheric radiative feedbacks associated with transient climate change and climate variability - Robert A. Colman; Scott B. Power (Climate Dynamics, 2010)

Mercury Sources to Lake Ozette and Lake Dickey: Highly Contaminated Remote Coastal Lakes, Washington State, USA - Chad Van Furl; John A. Colman; Michael H. Bothner (Water, Air, & Soil Pollution, 2010)

Polar lipid remodeling and increased sulfatide expression are associated with the glioma therapeutic candidates, wild type p53 elevation and the topoisomerase-1 inhibitor, Irinotecan - Huan He; Carol L. Nilsson; Mark R. Emmett; Yongjie Ji; Alan G. Marshall; Roger A. Kroes; Joseph R. Moskal; Howard Colman; Frederick F. Lang; Charles A. Conrad (Glycoconjugate Journal, 2010)

On the contribution of local feedback mechanisms to the range of climate sensitivity in two GCM ensembles - M. J. Webb; C. A. Senior; D. M. H. Sexton; W. J. Ingram; K. D. Williams; M. A. Ringer; B. J. McAvaney; R. Colman; B. J. Soden; R. Gudgel; T. Knutson; S. Emori; et al. (Climate Dynamics, 2006)

Mono-allelic Expression of Variegating Transgene Locus in the Mouse - Margaret L. Opsahl; Anthea Springbett; Richard Lathe; Alan Colman; Margaret McClenaghan; C. Bruce A. Whitelaw (Transgenic Research, 2003)

Statistical prediction of global sea‐surface temperature anomalies - A. W. Colman; M. K. Davey (International Journal of Climatology, 2003)
Sea‐surface temperature (SST) is one of the principal factors that influence seasonal climate variability, and most seasonal prediction schemes make use of information regarding SST anomalies. In particular, dynamical atmospheric prediction models require global gridded SST data prescribed through the target season. The simplest way of providing those data is to persist the SST anomalies observed at the start of the forecast at each grid point, with some damping, and this strategy has proved to be quite effective in practice. In this paper we present a statistical scheme that aims to improve that basic strategy by combining three individual methods together: simple persistence, canonical correlation analysis (CCA), and nearest‐neighbour regression. Several weighting schemes were tested: the best of these is one that uses equal weight in all areas except the east tropical Pacific, where CCA is preferred. The overall performance of the combined scheme is better than the individual schemes. The results show improvements in tropical ocean regions for lead times beyond 1 or 2 months, but the skill of simple persistence is difficult to beat in the extratropics at all lead times. Aspects such as averaging periods and grid size were also investigated: results showed little sensitivity to these factors. The combined statistical SST prediction scheme can also be used to improve statistical regional rainfall forecasts that use SST anomaly patterns as predictors. Copyright © Crown Copyright 2003. Published by John Wiley & Sons, Ltd.

Paleolimnology of Lake Tanganyika, East Africa, over the past 100 kyr - Christopher A. Scholz; John W. King; Geoffrey S. Ellis; Peter K. Swart; J. Curt Stager; Steven M. Colman (Journal of Paleolimnology, 2003)

STOIC: a study of coupled model climatology and variability in tropical ocean regions - Davey M.; Huddleston M.; Sperber K.; Braconnot P.; Bryan F.; Chen D.; Colman R.; Cooper C.; Cubasch U.; Delecluse P.; DeWitt D.; Fairhead L.; et al. (Climate Dynamics, 2002)

ENSIP: the El Niño simulation intercomparison project - M. Latif; K. Sperber; J. Arblaster; P. Braconnot; D. Chen; A. Colman; U. Cubasch; C. Cooper; P. Delecluse; D. Dewitt; L. Fairhead; G. Flato; et al. (Climate Dynamics, 2001)

Aircraft Measurements of Dimethyl Sulfide (DMS) Using a Whole Air Sampling Technique - I. J. Simpson; J. J. Colman; A. L. Swanson; A. R. Bandy; D. C. Thornton; D. R. Blake; F. S. Rowland (Journal of Atmospheric Chemistry, 2001)

On the vertical extent of atmospheric feedbacks - R. A. Colman (Climate Dynamics, 2001)

Growth and tissue mass cycles in the infaunal bivalve Yoldia eightsi at Signy Island, Antarctica - L. S. Peck; J. G. Colman; A. W. A. Murray (Polar Biology, 2000)

Inter-decadal modulation of the impact of ENSO on Australia - S. Power; T. Casey; C. Folland; A. Colman; V. Mehta (Climate Dynamics, 1999)

Biogenic silica from the BDP93 drill site and adjacent areas of the Selenga Delta, Lake Baikal, Siberia - Steven M. Colman; John A. Peck; Josephine Hatton; Eugene B. Karabanov; John W. King (Journal of Paleolimnology, 1999)

Towards the prediction of the East Africa short rains based on sea-surface temperature–atmosphere coupling - C. C. Mutai; M. N. Ward; A. W. Colman (International Journal of Climatology, 1998)

Non-linear climate feedback analysis in an atmospheric general circulation model - R. A. Colman; S. B. Power; B. J. McAvaney (Climate Dynamics, 1997)